Ergonomic endocrinology - Sanjay Kalra,; Atul Dhingra,; Nitin Kapoor, (Journal of the Pakistan Medical Association, 2024)
In this opinion piece, we introduce the concept of ergonomic endocrinology. Ergonomic endocrinology is defined as the bidirectional and multifaceted relationship between endocrine health and dysfunction on one hand, and ergonomic design and engineering on the other. We describe the various domains of ergonomic endocrinology, using the classification rubric of physical, cognitive and organizational ergonomics. We highlight ways in which endocrinology can contribute to the enhancement of ergonomics Keywords: Diabetes, hypoglycaemia, person centred care, PCOS, sarcopenia, Vitamin D.